2015
DOI: 10.1175/jcli-d-14-00739.1
|View full text |Cite
|
Sign up to set email alerts
|

The Continuum of Wintertime Southern Hemisphere Atmospheric Teleconnection Patterns*,+

Abstract: This study uses the method of self-organizing maps (SOMs) to categorize the June–August atmospheric teleconnections in the 500-hPa geopotential height field of the Southern Hemisphere (SH) extratropics. This approach yields 12 SOM patterns that provide a discretized representation of the continuum of SH teleconnection patterns from 1979 to 2012. These 12 patterns are large in spatial scale, exhibiting a mix of annular mode characteristics and wave trains of zonal wavenumber varying from 2 to 4. All patterns va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 102 publications
0
16
0
Order By: Relevance
“…Matthews and Meredith (2004) demonstrated that the austral winter southern hemisphere annular mode strengthens about 7 days after the peak in Indian Ocean MJO convection. A recent study by Chang and Johnson (2015) identified teleconnection patterns in the midlatitudes of Southern Hemisphere winter that exhibit oscillatory behavior on time scales of 20-30 days and with the frequency of occurrence modulated by the MJO phases. These patterns mix characteristics of the southern hemisphere annular modes (Limpasuvan & Hartmann, 1999;Thompson & Woodworth, 2014) and the asymmetric PSA modes.…”
Section: Southern Hemispherementioning
confidence: 99%
“…Matthews and Meredith (2004) demonstrated that the austral winter southern hemisphere annular mode strengthens about 7 days after the peak in Indian Ocean MJO convection. A recent study by Chang and Johnson (2015) identified teleconnection patterns in the midlatitudes of Southern Hemisphere winter that exhibit oscillatory behavior on time scales of 20-30 days and with the frequency of occurrence modulated by the MJO phases. These patterns mix characteristics of the southern hemisphere annular modes (Limpasuvan & Hartmann, 1999;Thompson & Woodworth, 2014) and the asymmetric PSA modes.…”
Section: Southern Hemispherementioning
confidence: 99%
“…The SOM method is a neural network-based cluster analysis that classifies a high-dimensional data set into representative patterns, using a neighborhood function to topologically order the high-dimensional input and group similar clusters together [Kohonen, 1998]. The SOM has recently been used to extract patterns of climate variation such as the El Niño-Southern Oscillation [Johnson, 2013] and Northern and Southern Hemisphere teleconnection patterns [Chang and Johnson, 2015;Johnson et al, 2008]. In addition, Chattopadhyay et al [2008] employed SOM analysis to characterize intraseasonal oscillation of the Indian summer monsoon, and Chu et al [2012] used it to extract intraseasonal modes of the East Asian-western North Pacific summer monsoon.…”
Section: Self-organizing Mapmentioning
confidence: 99%
“…This choice provides nine synoptic modes in total. Previous studies described ways to objectively examine if SOM patterns are distinguishable when the data samples are independent or weakly dependent (e.g., Chang & Johnson, ; Johnson, ). However, as the consecutive maps used in this study are highly dependent, there is no objective method (to the extent of the authors knowledge) to examine whether the SOM patterns are distinguishable.…”
Section: Measurements and Methodologymentioning
confidence: 99%